دور القيادة الاستراتيجية في تحقيق التحول الرقمي دراسة حالة جامعة محمد بوضياف بالمسيلة - زابي, صالح; بعطيش, شعبان (جامعة الوادي - University of eloued, 2021)
ملخص: هدفت هذه الدراسة إلى إبراز دور القيادة الاستراتيجية من خلال أبعادها الخمسة (تحديد التوجه الاستراتيجي، استغلال واستثمار القدرات والمواهب الاستراتيجية، تطوير راس المال البشري، مساندة وتعزيز الثقافة التنظيمية، تنفيذ الرقابة التنظيمية المتوازنة) في تحقيق التحول الرقمي، وذلك من خلال دراسة الارتباط والتأثير بين المتغيرين المذكورين وأبعادهما الفرعية حيث تكون مجتمع الدراسة من إطارات جامعة محمد بوضياف والممثلين للقيادة الاستراتيجية والبالغ عددهم 36 إطار، وقد أستخدم المنهج التحليلي الوصفي للوصول إلى نتائج الدراسة، والاعتماد على عدة أساليب إحصائية لتحليل البيانات. توصلت الدراسة إلى مجموعة من الاستنتاجات أهمها وجود علاقة ارتباط وتأثير قوية بين أبعاد القيادة الاستراتيجية والتحول الرقمي لجامعة محمد بوضياف، وهذا ما لمسناه في تحليل نتائج الدراسة بمقابلة مباشرة مع القائد الاستراتيجي المتمثل في شخص مدير جامعة محمد بوضياف بالمسيلة والذي أثرى محتوى هذه الدراسة بكثير من التعليقات والتحليلات على النتائج المتحصل عليها، وبناء على ما سبق قدم الباحثين مجموعة من التوصيات. Abstract: This study aimed at highlighting the role of strategic leadership through its five dimensions (determining the strategic direction, exploiting and investing strategic capabilities and talents, developing human capital, supporting and enhancing organizational culture, and implementing balanced organizational control) in achieving digital transformation, by studying the link and influence between the two aforementioned variables and their sub-dimensions. The study population consisted of 36 of the university's executives and representatives of strategic leadership. To arrive at the results of the study, a descriptive analytical approach was adopted; the study also relied on several statistical methods to analyse the data at hands. The current study reached a set of conclusions, the most important of which is the existence of a strong correlation and influence between the dimensions of strategic leadership and the digital transformation of the University of Muhammad Boudiaf, and this is what we observed in the analysis of the results of the study whilst conducting an interview with a strategic leader, that is the director of Muhammad Boudiaf University, M'sila, who helped enrich the content of this study with several comments and analyses based on the results obtained. Finally, and based on the above, the researchers presented a set of recommendations.
The Role of Strategic Leadership in Achieving Digital Transformation. The Case of Mohamed Boudiaf University, M'sila
مقال
Keywords: قيادة ; قيادة استراتيجية ; أبعاد القيادة الاستراتيجية ; رقمنة ; تحول الرقمي